Emily Windsnap and the Siren's Secret : Emily Windsnap #4 - Kessler, Liz (Somerville, Mass. : Candlewick Press, 2010)
When Neptune tells Emily and her merman father and human mother to return to Brightport to try to make merpeople and humans work more closely together, Emily faces problems with old enemies, her new, half-merfolk friend Aaron, and a mystery related to a group of legendary lost sirens.
Keywords: Mermaids -- Fiction; Interpersonal relations -- Fiction; Neptune (Roman deity) -- Fiction; Sirens (Mythology) -- Fiction